Management of Exfoliative Cheilitis - Sarah Mersil; NIcholas Limanda (Universitas Sam Ratulangi, 2022)
Abstract: Cheilitis is an inflammation of the vermilion border of lips. Exfoliative cheilitis occurs on the upper and lower lips in the form of exfoliation of the keratinized surfaceâ€™s lips, accompanied by redness and edema. We reported a 21-year-old female patient, a dental student, with a chief complaint of sores on the cracked lower and upper lips, and bleeding since two weeks ago. She was not sure when this condition started, but she had realized it for almost three years. The patient used to feel dry lips, therefore she licked and sucked her lips and then peeled the dry surface off. She did not drink enough water, did not like fruits and vegetables very well, and was allergic to certain lipsticks, so, she discontinued using it since one year ago. She treated her lips with lip balm, but it did not show any improvement. Extraoral examination showed that the lower lip was not covered by epithelia, there was a blackish red crust of 1 cm around the vermilion border mixed with exfoliating yellowish crust. Several fissures were seen on the upper and lower lips associated with erythema. This patient was diagnosed as exfoliative cheilitis and was managed with applying lip balm and triamcinolone acetonide 0.1%, twice a day that showed satisfying result. In conclusion, in managing exfoliative cheilitis, the causative factors have to be determined and controlled, and administration of topical steroid and moisturizer showed significant improvement.Keywords: exfoliative cheilitis; steroidsÂ Abstrak: Keilitis adalah adanya inflamasi pada vermilion border bibir. Kasus keilitis eksfoliatif terjadi pada bibir atas dan bawah berupa pengelupasan permukaan keratin bibir, disertai adanya kemerahan dan edema pada bibir. Kami melaporkan kasus seorang pasien perempuan 21 tahun, mahasiswi, dengan keluhan sariawan di bibir bawah dan atas tampak pecah-pecah, berdarah dan perih sejak dua minggu lalu. Tidak diketahui pasti sejak kapan kondisi ini dialami, namun mulai disadari sejak sekitar tiga tahun. Pasien sering merasa bibir kering, sering menjilat/menghisap bibir kemudian mengelupasnya. Kurang minum air, kurang menyukai buah-buahan dan sayur, serta alergi pemakaian lipstik tertentu dan sudah dihentikan sejak satu tahun lalu. Sudah melakukan pengobatan dengan lip balm, namun tidak menunjukkan perubahan. Pemeriksaan klinis ekstraoral menunjukkan sebagian besar bibir bawah tidak tertutupi epitel, terdapat krusta merah kehitaman Â±1cm sekitar batas vermilion bercampur dengan krusta kekuningan hampir mengelupas (eksfoliasi). Beberapa fisur terlihat pada bagian bibir atas dan bawah disertai eritema. Pasien didiagnosis sebagai keilitis eksfoliatif. Penatalaksanaan dengan melanjutkan pemakaian lip balm dan pemberian obat oles bibir triamcinolone acetonide 0,1%, dipakai dua kali sebelum penggunaan lip balm yang memberikan hasil memuaskan. Simpulan kasus ini ialah dalam penatalaksanaan kasus keilitis eksfoliatif harus ditentukan faktor penyebab dan dikendalikan. Pemberian steroid topikal dan pelembab memberikan perbaikan yang berarti.Kata kunci: keilitis eksfoliatif; steroid